REFINEMENT OF THE FANTASY GENRE THROUGH THE WORKS OF URSULA LE GUIN (Academicia Globe: Inderscience Research, 2024)
This scientific article talks about the improvement of the fantasy genre. This field is little studied in our country, but as a structural and important element of the work of Le Guin, one of the modern writers, the main attention is paid to the myth-based improvement of different worlds and cultures. The issues discussed in Le Guin's works relate to the fundamental human values that give special importance to his works in the modern world, which is experiencing a fundamental spiritual-civilizational crisis. The writer's works have gone far beyond the borders of mass literature and culture. We are raising "fantasy" to the level of classic fiction with strong philosophical and aesthetic potential.